Application of Nanodrug Delivery Systems in Enhancing Treatment of Gastritis and Gastric Cancer: A Systematic Evaluation of Targeted Therapy - Miaomiao Xu; Shujie Tian; Jing Wang; Shuqing Gan; Ziting Zhang; Lixing Weng (Pharmaceutics)
In recent years, nanomedicine has been emerging as a promising therapeutic approach in the treatment of gastritis and gastric cancer, particularly through targeted drug delivery systems and combination therapies that enhance therapeutic effects. Gastritis and gastric cancer, being common gastrointestinal diseases, often exhibit suboptimal treatment outcomes due to the limitations of traditional medications. Interventions based on nanotechnology not only improve the local concentration and bioavailability of drugs but also promote precise targeted therapy by regulating drug release rates, while minimizing adverse side effects, thereby enhancing therapeutic efficacy. Despite significant progress in basic research and preclinical applications, the clinical translation of nanomedicine still faces numerous challenges, including stability, biocompatibility, production standardization, regulatory and ethical barriers, as well as optimization of clinical trial designs. Furthermore, combining nanomedicine with other therapeutic modalities, such as immunotherapy and gene therapy, may open new avenues for addressing complex digestive system diseases. Future research should continue to explore the potential of nanocarriers, particularly in the formulation and stability of nanomaterials for precision therapy, with the aim of improving the quality of life and survival rates for patients with gastritis and gastric cancer.